Ruxolitinib and decitabine plus a busulfan–cyclophosphamide conditioning regimen for relapse prophylaxis in patients with high-risk acute myeloid leukemia or myelodysplastic syndromes - Wei, Yujun; Luan, Songhua; Wang, Lu; Wang, Lili; Li, Fei; Jin, Xiangshu; Yang, Ruoling; Qian, Kun; Peng, Bo; Tang, Jingwen; Zhang, Haoyang; Dou, Liping; et al. (Frontiers in Immunology, 2025)
PurposeRelapse remains the leading cause of treatment failure in high-risk acute myeloid leukemia (AML) or myelodysplastic syndrome-IB (MDS-IB) patients after allogeneic hematopoietic stem cell transplantation (allo-HSCT). Ruxolitinib has demonstrated antileukemic activity in vitro, and decitabine has been found to be tolerable when combined with modified busulfan–cyclophosphamide (mBu/Cy) conditioning regimen. Here, we investigated the efficacy of ruxolitinib and decitabine plus a mBu/Cy conditioning regimen (Rux-Dec-mBu/Cy) in reducing relapse in high-risk AML/MDS patients (ClinicalTrials.gov identifier: NCT04582604).Patients and methodsThis prospective investigational study enrolled 58 patients between May 2020 and July 2023. These patients had either a relapsed/refractory status, remission status with adverse genetic abnormalities or positive measurable residual disease (MRD+) prior to conditioning. Ruxolitinib (days –15 to –1) and decitabine (days –15 to –10) were administered, followed by mBu/Cy conditioning. The outcomes of a historical cohort of 58 patients (matched 1:1) who received mBu/Cy are described for reference.ResultsAll 58 patients achieved engraftment. With a median follow-up of 967 (464–1597) days, the 2-year cumulative incidence of relapse was 19.0%. The probabilities of 2-year overall survival (OS), disease-free survival (DFS) and graft-versus-host disease-free, relapse-free survival (GRFS) were 70.3%, 70.6% and 65.2%, respectively. The cumulative incidence of grade II-IV acute graft-versus-host disease (aGVHD) was 44.1%. The most common grade ≥3 adverse event was oropharyngeal mucositis (8.6%, n=5). Within 6 months post-transplantation, the cumulative incidence of cytomegalovirus (CMV) reactivation was 34.5%, and that of Epstein–Barr virus (EBV) reactivation was 62.1%.ConclusionsThis investigational study revealed that the Rux-Dec-mBu/Cy conditioning was tolerable and reduced relapse in high-risk AML/MDS patients.